PERENCANAAN SISTEM IRIGASI TETES (DRIP IRRIGATION) DI DESA BESMARAK KABUPATEN KUPANG - Udiana, I Made; Bunganaen, Wilhelmus; Pa Padja, Rizky A. (Jurnal Teknik Sipil, 2014)
Water is an important natural resource for human needs one of them in agriculture . Village Community Besmarak mostly farmers who use wells as the main source of water . How to water provision applied by the villagers of Besmarak not effective , efficient and the results are uneven . The drip irrigation system is one of the alternatives in resolving the matter. The drip irrigation system is the provision of water to the plant continuously around the root zone of plants . The main components in a drip irrigation system is the emitter (dropper) , lateral pipes , pipe divider , main pipes , water pumps , and other ancillary components. In planning a drip irrigation system in the village Besmarak , plants in the review is the tomato plant. Value of reference evapotranspiration (ETo) was calculated with the program cropwat 8.0 ranged from 4.32 to 7.47 mm/day and the value of crop evapotranspiration (ETc) ranged from 2.97 to 6.89 mm/day . Effective precipitation ranged from 0 to 63.2 mm/month . Discharge emitters are selected to meet the water needs of the plant is 4 l/ h and substantial rate of droplet emitternya ie 11,428 mm/hour . Based on calculations of power pumps used to lift water to land is 0.5 kW.